The Effect of Xylitol on the Composition of the Oral Flora: A Pilot Study - Söderling, Eva; Hirvonen, Aino; Karjalainen, Sara; Fontana, Margherita; Catt, Diana; Seppä, Liisa (European Journal of Dentistry, 2011)
Objectives: Our aim was to investigate the effect of short-term xylitol consumption on the microbial composition of plaque and saliva. Methods: Twelve volunteers (22-38 yrs) harboring mutans streptococci (MS) participated in the randomized, double-blind, cross-over study. The experimental chewing gum contained 65% xylitol while the control gum contained 63% sorbitol and 2% maltitol w/w. The polyol dose was approximately 6 g/day. Stimulated saliva and plaque samples were collected before and after the two four-week test periods. The samples were cultured for MS, total streptococci, lactobacilli, and total facultatives. A part of the samples were subjected to DNA-DNA hybridizations of 14 microbial plaque species: Actinomyces naeslundii, A. viscosus, Fusobacterium nucleatum, Lactobacillus acidophilus, L. fermentum, L. paracasei, L. rhamnose, L. plantarum, Streptococcus gordonii, S. oralis, S. parasanguis, S. salivarius, S. sanguinis, Veillonella parvula. Results: The MS counts of the plaque samples collected from “caries-prone” tooth sites decreased significantly (P<.01) in the xylitol gum group but not in the sorbitol gum group. Also the plaque MS percentage decreased significantly in the xylitol gum group (P<.01). The salivary MS counts did not decrease either in the xylitol or in the sorbitol gum groups. Nor were changes detected in the salivary levels of total streptococci or lactobacilli. The DNA-DNA hybridization assay revealed no study-induced changes in the microbial composition of the dental plaque. Conclusions: Within the limitations of this pilot study, xylitol consumption reduced MS counts in plaque but appeared not to affect the microbial composition of plaque or saliva in general. (Eur J Dent 2011;5:24-31)
Keywords: Xylitol; Mutans streptococci; Plaque; Oral flora; Chewing gum